2023
DOI: 10.3390/ijms24108550
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Response in COVID-19 Depending on the Severity of the Disease and the Vaccination Status

Abstract: The aim of this study was to analyze the serum concentration of interleukin-6 (IL-6), C-reactive protein (CRP), D-dimer, lactate dehydrogenase (LDH), ferritin, and procalcitonin in COVID-19 patients with different forms of the disease. We performed a prospective cohort study on 137 COVID-19 consecutive patients, divided into four groups according to the severity of the disease as follows: 30 patients in the mild form group, 49 in the moderate form group, 28 in the severe form group, and 30 in the critical form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…Fatima et al 2022 [ 19 ] reported the similar findings that, the mean values of D-dimer and serum troponin-1 were higher for unvaccinated individuals (1.2, 0.25) than fully vaccinated individuals (0.8, 0.05). Trofin et al 2023 [ 20 ] reported the higher mean values of CRP levels in vaccinated individuals of CoVid-19 infection. The mean value of Platelet levels in unvaccinated CoVid-19 infected group (4.34±6.6) was higher than vaccinated group (1.51±4.32) and these results agreed with the findings of Ostrowski et al 2021 [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fatima et al 2022 [ 19 ] reported the similar findings that, the mean values of D-dimer and serum troponin-1 were higher for unvaccinated individuals (1.2, 0.25) than fully vaccinated individuals (0.8, 0.05). Trofin et al 2023 [ 20 ] reported the higher mean values of CRP levels in vaccinated individuals of CoVid-19 infection. The mean value of Platelet levels in unvaccinated CoVid-19 infected group (4.34±6.6) was higher than vaccinated group (1.51±4.32) and these results agreed with the findings of Ostrowski et al 2021 [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that the authors classify the severity of COVID-19 by incorporating diagnostic codes of other comorbid conditions or the types of medications administered to patients. 2,3 This approach may help elucidate the risk of subsequent herpes zoster in COVID-19 patients across various severity levels.…”
Section: Long-term Risk Of Herpes Zoster Following Covid-19: a Retros...mentioning
confidence: 99%
“…Wen-Bin Yeh 2 Hui-Yuan Chen 3 Su-Boon Yong 4 1 School of Medicine, Chung Shan Medical University, Taichung, Taiwan 2 Department of Emergency Medicine,…”
Section: Shih-wei Huangmentioning
confidence: 99%
“…The study by Trofin et al aimed to examine the serum concentrations of interleukin-6 (IL-6), C-reactive protein (CRP), D-dimer, lactate dehydrogenase (LDH), ferritin, and procalcitonin in COVID-19 patients with varying disease severity [ 43 ]. A prospective cohort study was conducted, involving 137 consecutive COVID-19 patients, who were categorized into four groups based on disease severity: 30 patients with mild symptoms, 49 with moderate symptoms, 28 with severe symptoms, and 30 with critical symptoms.…”
Section: An Overview Of Published Articlesmentioning
confidence: 99%